New method for control of fuel injection initiation and fuel combustion in diesel locomotive engines - A. Yu. Kon’kov; I. D. Kon’kova (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
Adequate regulation of diesel engine fuel equipment is an important factor affecting the economic and ecological indicators of diesel engine and its reliability. The fuel injection advance angle deviates from the best value during operation for several reasons, requiring timely control and regulation of the parameter. This issue is crucial for diesel engines with individual high-pressure pumps like the diesel locomotive engines. This study presents a new method for indirect determination of the fuel injection advance angle based on analysis of the pressure fi rst-order derivative signal — pressure change rate. This method eliminates the need for additional measurements like the crankshaft rotation angle or piston position, and therefore, exhibits potential for the development of easy and reliable devices for online diagnostics. The study also briefl y analyzes control methods for the fuel injection advance angle used in operating diesel-electric locomotives in Russia. The results of theoretical research performed through mathematical modeling for the locomotive diesel engine 1А-5D49 is also examined. A dimensionless criterion is proposed based on results calculated from the experiment, which is determined by the value of the pressure change rate signal at representative points allowing calculation of the fuel injection advance angle using simple linear dependence. Verifi cation of the proposed method demonstrates good agreement of the results with existing methods.